PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN TERHADAP KINERJA APARAT PEMERINTAH DENGAN KEPUASAN KERJA DAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERASI (Studi Empiris Pada Dinas Di Lingkungan Pemerintah Daerah Kota Palu) - Tapussa, Agnesia (Katalogis, 2015)
This study is aimed to explore and analyze: 1) budget drafting participation, government officials’ performance, job satisfaction, and organizational commitment in Palu governmental offices; 2) the effect of budget drafting participation on officials’ performance; 3) whether job satisfaction moderates the influence of budget drafting participation on officials’ performance; 4) whether organizational commitment moderates budget drafting participation on officials’ performance. The population consists of 1036 people with 91 samples selected, including heads of office, secretaries, and head sections. The result shows that: 1) budget drafting participation has significant effects on officials’ performance in Palu governmental offices; 2) job satisfaction moderates the effects of budget drafting participation on officials’ performance significantly; 3) organizational commitment moderates the effects of budget drafting participation on officials’ performance in Palu governmental office.